Study on scenarios and requirements of 6G distributed network - Song Yaqin; Xu Hui (Dianzi Jishu Yingyong)
To meet the future industry application requirements, the 6G network needs to build a high-performance, highly flexible, and highly reliable network. Starting from the scenarios and requirements of the 6G distributed network, this study designs a 6G distributed network architecture composed of central network nodes and distributed network nodes, and proposes key technologies such as information interaction at the network node granularity, service continuity assurance, network autonomy, and networking coordination. The research results show that this architecture and key technologies can effectively support the diversified services and flexible deployment of the 6G network, providing theoretical support and practical guidance for the development of 6G networks.